Jat - Sunil K. Khanna (Encyclopedia of Medical Anthropology, 2004)
Fine particulate matter (PM2.5) serves as a significant carrier of toxic heavy metals and poses potential health risks, particularly for children in school environments. However, limited studies have systematically compared school settings across cities with differing industrial profiles, resulting in a critical gap in understanding spatial variations in exposure risks. This study characterized the concentrations, seasonal variability, sources, and inhalation health risks of five PM2.5-bound metals, namely Cu, Cd, Ni, Pb, and Zn, in schools from two contrasting cities in Guangdong Province, China: Guangzhou and Maoming. PM2.5 samples were collected from 20 schools during summer and winter of 2018 and analyzed by inductively coupled plasma mass spectrometry. Pollution status, assessed using the geoaccumulation index (Igeo) and enrichment factor (EF), indicated that PM2.5-bound metals in both Guangzhou and Maoming were predominantly of anthropogenic origin, with Cu and Cd exhibiting the highest enrichment and contamination levels, whereas Ni and Pb were largely associated with natural background sources and Zn reflected mixed origins. Principal component analysis (PCA) was used to identify dominant sources of heavy metals and support source apportionment. The noncarcinogenic and carcinogenic risks were assessed for children and adults. Across both cities, Cu (471.19) showed the highest mean concentrations, followed by Zn, Pb, Ni, and Cd, with winter values generally exceeding summer values. Guangzhou exhibited stronger anthropogenic enrichment than Maoming, particularly for Cu (27.72) and Cd (27.32), indicating greater influence from traffic, industrial combustion, and urban emissions. Correlation analysis suggested common and seasonally enhanced sources in winter. Health risk assessment showed that all hazard quotients and carcinogenic risk values were below accepted thresholds, indicating low immediate inhalation risk. However, children experienced higher exposure than adults, and Pb (4.85E-03) and Cu (3.27E-03) contributed most to noncarcinogenic risk, while Cd (7.30E-06) and Ni (2.21E-06) posed the main carcinogenic concern. Overall, the results highlight the need for continued source control in school environments, with special attention to nonexhaust traffic emissions and industrial combustion.